Alternative trafficking of Weibel‐Palade body proteins in CRISPR/Cas9‐engineered von Willebrand factor–deficient blood outgrowth endothelial cells. Issue 4 (1st August 2019) - Schillemans, Maaike; Kat, Marije; Westeneng, Jurjen; Gangaev, Anastasia; Hofman, Menno; Nota, Benjamin; van Alphen, Floris P. J.; de Boer, Martin; van den Biggelaar, Maartje; Margadant, Coert; Voorberg, Jan; Bierings, Ruben
Abstract: Background: Synthesis of the hemostatic protein von Willebrand factor (VWF) drives formation of endothelial storage organelles called Weibel‐Palade bodies (WPBs). In the absence of VWF, angiogenic and inflammatory mediators that are costored in WPBs are subject to alternative trafficking routes. In patients with von Willebrand disease (VWD), partial or complete absence of VWF/WPBs may lead to additional bleeding complications, such as angiodysplasia. Studies addressing the role of VWF using VWD patient–derived blood outgrowth endothelial cells (BOECs) have reported conflicting results due to the intrinsic heterogeneity of patient‐derived BOECs. Objective: To generate a VWF‐deficient endothelial cell model using clustered regularly interspaced short palindromic repeats (CRISPR) genome engineering of blood outgrowth endothelial cells. Methods: We used CRISPR/CRISPR‐associated protein 9 editing in single‐donor cord blood–derived BOECs (cbBOECs) to generate clonal VWF −/− cbBOECs. Clones were selected using high‐throughput screening, VWF mutations were validated by sequencing, and cells were phenotypically characterized. Results: Two VWF −/− BOEC clones were obtained and were entirely devoid of WPBs, while their overall cell morphology was unaltered. Several WPB proteins, including CD63, syntaxin‐3 and the cargo proteins angiopoietin (Ang)‐2, interleukin (IL)‐6, and IL‐8 showed alternative trafficking and secretion in the absence of VWF. Interestingly, Ang‐2 was relocated to the cell periphery and colocalized with Tie‐2. Conclusions: CRISPR editing of VWF provides a robust method to create VWF‐ deficient BOECs that can be directly compared to their wild‐type counterparts. Results obtained with our model system confirmed alternative trafficking of several WPB proteins in the absence of VWF and support the theory that increased Ang‐2/Tie‐2 interaction contributes to angiogenic abnormalities in VWD patients.